A case of intestinal obstruction due to inflammatory changes in the small intestine from alkaline ingestion. Issue 3 (9th March 2018) - Maruhashi, Takaaki; Hanajima, Tasuku; Nakatani, Kento; Hattori, Jun; Takeuchi, Ichiro; Kataoka, Yuichi; Asari, Yasushi
Abstract : Case: Alkaline ingestion frequently causes corrosive esophagitis but rarely causes lower digestive tract injury. In this case, a 79‐year‐old man accidentally drank kitchen detergent. After 3 h, lower abdominal pain occurred and gradually worsened. He was taking a proton pump inhibitor after proximal gastrectomy for gastric cancer. He had local tenderness in the left lower abdomen. Abdominal computed tomography showed expansion of the small intestine, thickening of the intestinal wall, and inflammatory changes. Upper gastrointestinal endoscopy showed no obvious injury to the esophagus or stomach. Outcome: Conservative treatment with an ileus tube was undertaken for intestinal obstruction caused by alkaline ingestion. There were no complications, such as gastrointestinal perforation, and he was discharged on day 17. Conclusion: Alkaline ingestion may cause injuries not only to the upper but also to the lower digestive tract in patients who are taking proton pump inhibitors or have had gastrectomy. Abstract : Alkaline ingestion frequently causes corrosive esophagitis but rarely causes lower digestive tract injury. Alkaline ingestion may cause injuries not only to the upper but also to the lower digestive tract in patients who are taking proton pump inhibitors or have undergone gastrectomy.